Hangil Book Hall and Camera Obscura (Oz, 2005)
In fall of 2001, SHoP Architects received the commission for a building for the Heyri Art Valley master plan currently being executed one hour north of Seoul, South Korea in the city of Paju in the Province of Kyong-gi Do. The project is being planned by M.A.R.U. (Metropolitan Architecture Research Unit), a local firm, on land comprised of six hills and valleys with a change in elevation of 94 meters.